2017
DOI: 10.1097/md.0000000000005970
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance spectroscopy can precisely discriminate human breast carcinoma from benign tumors

Abstract: Intraoperative frozen pathology is critical when a breast tumor is not diagnosed before surgery. However, frozen tumor tissues always present various microscopic morphologies, leading to a high misdiagnose rate from frozen section examination. Thus, we aimed to identify breast tumors using bioimpedance spectroscopy (BIS), a technology that measures the tissues’ impedance. We collected and measured 976 specimens from breast patients during surgery, including 581 breast cancers, 190 benign tumors, and 205 normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…BIS analyzer Mscan1.0B (Sealand Technology, Chengdu, Sichuan, China) was used in this study, which generated BIS data of breast specimens by sweep frequency measurement ranging from 3 kHz to 1 MHz. Because China did not have a national standard of medical impedance analysis system, this study used the standard of the Medical Equipment Monitoring Center of Sichuan Province.…”
Section: Methodsmentioning
confidence: 99%
“…BIS analyzer Mscan1.0B (Sealand Technology, Chengdu, Sichuan, China) was used in this study, which generated BIS data of breast specimens by sweep frequency measurement ranging from 3 kHz to 1 MHz. Because China did not have a national standard of medical impedance analysis system, this study used the standard of the Medical Equipment Monitoring Center of Sichuan Province.…”
Section: Methodsmentioning
confidence: 99%
“…With the discovery of marked differences between the electrical impedances of malignant breast tissues and healthy tissues 1 , 2 , bioelectrical impedance technology has emerged as a new approach for breast cancer detection. This technology is noninvasive, cost-effective, safe, informative, and easily acceptable to both doctors and patients 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Because the current has to pass around the cells with path of least resistance, the resistance to flow depends on the cell spacing and how they are arranged, whereas with increasing frequencies current can penetrate the membrane and hence passes through both intracellular and extracellular spaces 9 . Cellular changes alter the flow of electrical current through living tissue, and a number of literatures indicated differences in human electrical impedance between benign and malignant tumors [breast 13,14 , thyroid [15][16][17] , prostate 18 , bladder 19 , colon 20 ]. Previous studies have confirmed the feasibility of EIS in diagnosis of thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%